Electrochemical Impedance Spectroscopy for Monitoring of Alkaline Phosphatase Reaction with Substrate. (2017) - Ferancova, Adriana; Hattuniemi, Maarit; Pääkkönen, Satu; Tervo, Pirkko; Ohtonen, Elisa; Sesay, Adama; Räty, Jarkko; Virtanen, Vesa
Abstract: Electrochemical impedance spectroscopy was compared to square wave voltammetry for monitoring the reaction between alkaline phosphatase and its substrates.